2019
DOI: 10.1111/anu.13004
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing diets to decrease environmental impact of Nile tilapia (Oreochromis niloticus) production

Abstract: Aquaculture is one of the most thriving animal production sectors, and Nile tilapia (Oreochromis niloticus) farming represents 8% of total finfish culture. However, the industry sustainability depends on the development of cost‐effective and environmental friendly feeds. This study aimed to reduce dietary protein levels in diets for juvenile tilapia and to minimize diet environmental impact while maximizing biological efficiency. A growth trial was performed using five isoenergetic plant protein‐based diets wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…In the present study, the LowL diet resulted in less (p < .05) growth than the BalL diet. This finding agrees with previous studies, which reported that the growth performance, feed intake and feed conversion ratio of Nile tilapia were optimal at a dietary lysine level of 28-36 g kg −1 CP (Teodósio et al, 2020); digestible protein (Furuya et al, 2012) and protein retention were significantly higher in tilapia fed 30 g kg −1 CP (Teodósio et al, 2020). It was also previously observed that daily weight gain was better in Nile tilapia (27.5 g kg −1 ) fed a diet containing 55.5 g lysine kg −1 CP, than in Nile tilapia fed a diet containing 43.9 g lysine kg −1 CP (Michelato et al, 2016).…”
Section: Fish Performance and Nitrogen Utilizationsupporting
confidence: 93%
“…In the present study, the LowL diet resulted in less (p < .05) growth than the BalL diet. This finding agrees with previous studies, which reported that the growth performance, feed intake and feed conversion ratio of Nile tilapia were optimal at a dietary lysine level of 28-36 g kg −1 CP (Teodósio et al, 2020); digestible protein (Furuya et al, 2012) and protein retention were significantly higher in tilapia fed 30 g kg −1 CP (Teodósio et al, 2020). It was also previously observed that daily weight gain was better in Nile tilapia (27.5 g kg −1 ) fed a diet containing 55.5 g lysine kg −1 CP, than in Nile tilapia fed a diet containing 43.9 g lysine kg −1 CP (Michelato et al, 2016).…”
Section: Fish Performance and Nitrogen Utilizationsupporting
confidence: 93%
“…This condition was proved by a decline in blood protein value of 11.77%, which caused an increase in protein retention value of 33.03% compared to negative control (Table 4). Additionally, improved protein utilization will reduce oxidative deamination processes (Michelato et al., 2016; Subramanian, 2013; Teodósio et al., 2019), thus improving fish growth (Suprayudi et al., 2011; Suprayudi, 2018) and decreasing the nitrogen excretion out of the body (Zupa et al, 2015). Furthermore, it could also lead to less threat of fish physiological stress due to waste accumulation in the water.…”
Section: Discussionmentioning
confidence: 99%
“…The present results confirmed compelling evidence for the importance of lysine and histidine supplementation in combination to optimize growth performance in grow-out Nile tilapia. Pereira et al, 2017;Teodósio et al, 2019;Trosvik et al, 2012). Previous researches have attributed the synergic effects of multiple amino acids supplementation on protein retention efficiency and consequently growth of grass carp, Ctenopharyngodon idella (Gan et al, 2012); Nile tilapia, (Nguyen et al, 2020) and rainbow trout, Oncorhynchus mykiss (Cheng et al, 2003).…”
Section: Discussionmentioning
confidence: 99%